A review of analysis the system of thermal power plant economics - Hussin, Muhammad Hazim; M Hussaen, El Hussaen; Ogab, Mohammed; Khalid, Amir; Ngadiron, Zuraidah (Penerbit UTHM, 2020)
Power plants are part of the infrastructure of modern society, and it is needed that these power plant facilities be constructed effectively to achieve a sophisticated level of reliability. The major economic factor in power system planning, operation, and control are with the expenses of generating real power. The analysis of general power plant economic determined the possibility to fulfil the need and optimized the power generation thus lowering the cost operation for the thermal power plant system. Several factors are essential to be considered to build a thermal power plant based on the factor discussed in this study. This study also includes maximizing and eliminating the thermal power plant losses and implements good power plant economics